Secretome profiling of Artemisia absinthium extract-loaded polymeric nanoparticle-treated MCF-7 and MDA-MB-231 revealed perturbation in microtubule assembly and cell migration - Kauser, Sana; Mughees, Mohd; Mangangcha, Irengbam Rocky; Swami, Sanskriti; Wajid, Saima (Frontiers in Oncology, 2023)
Introduction: Artemisia absinthium (wormwood) exhibits anticancer properties by inhibiting proliferation and causing cell death in breast cancer. Targeted drug-delivery of A. absinthium nanoformulation using N-isopropyl acrylamide, N-vinyl pyrrolidone, and acrylic acid based-polymeric nanoparticles (NVA-AA NPs) was ensured by utilizing features of tumor microenvironment, although their mechanism of action involved in cytotoxicity remain unknown.The present study employed nano LC-MS/MS to identify differences in secretory protein expression associated with treatment of Breast cancer cell lines (MCF-7; MDA MB-231) by NVA-AA NPs for determination of affected pathways and easily-accessible therapeutic targets. Different bioinformatics tools were used to identify signature differentially expressed proteins (DEPs) using survival analysis by GENT2 and correlation analysis between their mRNA expressions and sensitivity towards small-molecule drugs as well as immune cell infiltration by GSCA.: Analysis by GENT2 revealed 22 signature DEPs with most significant change in their expression regulation, namely Gelsolin, Alpha-fetoprotein, Complement component C3, C7, Histone H2B type 1-K, Histone H2A.Z, H2AX, Heat shock cognate 71 kDa protein, Heat shock 70 kDa protein 1-like, Cytochrome C somatic, GTP-binding nuclear protein Ran, Tubulin beta chain, Tubulin alpha-1B chain, Tubulin alpha-1C chain, Phosphoglycerate mutase 1, Kininogen 1, Carboxypeptidase N catalytic chain, Fibulin-1, Peroxiredoxins 4, Lactate dehydrogenase C, SPARC, and SPARC-like protein 1. Correlation analysis between their mRNA expressions versus immune cell infiltrates showed positive correlation with anti-tumor immune response elicited by these NPs as well as correlation with drug response shown by GDSC and CTRP drugs in different cancer cells. Discussion: Our results suggest that NVA-AA NPs were able to invade the tumor microenvironment, transformed the communication network between the cancer cells, affected potential drivers of microtubular integrity, nucleosome assembly, cell cycle, and eventually caused cell death.